2018
DOI: 10.1016/j.jphotobiol.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Enterococcus faecalis and Propionibacterium acnes to antimicrobial photodynamic therapy

Abstract: Bacterial resistance to available antibiotics nowadays is a global threat leading researchers around the world to study new treatment modalities for infections. Antimicrobial photodynamic therapy (aPDT) has been considered an effective and promising therapeutic alternative in this scenario. Briefly, this therapy is based on the activation of a non-toxic photosensitizing agent, known as photosensitizer (PS), by light at a specific wavelength generating cytotoxic singlet oxygen and free radicals. Virtually all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 45 publications
0
20
0
2
Order By: Relevance
“…It allows for the deep penetration of light in the biological tissues and expressive quantum yield for singlet oxygen formation [61,62]. The literature has already established the action of PDT mediated by MB, presenting its action against several bacteria associated with oral diseases [63,64]. MB has characteristics that promote good interaction with bacteria such as the positive charge on the molecule and low molecular mass.…”
Section: Discussionmentioning
confidence: 99%
“…It allows for the deep penetration of light in the biological tissues and expressive quantum yield for singlet oxygen formation [61,62]. The literature has already established the action of PDT mediated by MB, presenting its action against several bacteria associated with oral diseases [63,64]. MB has characteristics that promote good interaction with bacteria such as the positive charge on the molecule and low molecular mass.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative acne treatments include blue light, ultraviolet (UV) phototherapy, and photodynamic therapy [117,118,119]. These approaches could improve acne by reshaping the skin microbiota and lowering C. acnes counts within the lesions.…”
Section: Acne Treatment and Skin Microbesmentioning
confidence: 99%
“…Several studies have verified its photoinactivation ability when activated with the proper wavelengths of light [ 88 ]. CUR-based API could induce significant killing of Gram-positive E. faecalis cells [ 153 , 154 , 155 , 156 ]. Pileggi et al (2013) demonstrated that 10 µM of photoactivated CUR could completely inactivate E. faecalis biofilms after 30 min preincubation and 240-sec irradiation [ 156 ].…”
Section: Antimicrobial Photoinactivationmentioning
confidence: 99%
“…Furthermore, the required illumination doses have to be discussed and compared with general illumination conditions. RF can be excited by blue light and requires from 3 to 400 J/cm 2 according to the data available in the literature (see Table S1 of Supplementary Material ) [ 93 , 94 , 95 , 96 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 117 , 118 , 119 , 120 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 148 , 149 , 150 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 165 , 173 , 175 , 176 , 177 , 178 , 179 , 180 , 181 ,…”
Section: Illumination Requirements For Apimentioning
confidence: 99%